Identification of High School Students' Thinking Process Levels in Solving Geometry Problems Using Van Hiele's Theory - Claudia Betruchy Bada (Jurnal Amal Pendidikan, 2024)
This research aims to identify level of students’ thinking process in solving geometry problems based on Van Hiele’s theory. The Van Hiele’s theory is the theory of geometry thinking process, consist of level 0 visualization, level 1 analysis, level 2 informal de-duction, level 3 deduction, and level 4 rigor. The qualitative approach was used in this research. The participants were four voluntary students come from the second grade of Senior High School. Data collected by observation, test, and interview. The re-sults show that during the problem-solving process, the male students thinking process is at an analysis level or level 1 and female students are at an informal deduction level or level 2. The result of the research especially deals with students’ thinking level can be used as teachers information in preparing teaching strategies that appropriate with their students’ thinking especially in geometry. Furthermore, the result can be used to  minimilize other factors that inhibit students’ thinking process in solving geometry problems.